Long-term impacts of an unanticipated risk event: The 2007/08 food price crisis and child growth in Indonesia - Yamauchi, Futoshi; Larson, Donald F. (International Food Policy Research Institute, 2018)
Unanticipated spikes in food prices can increase malnutrition among the poor, with lasting consequences; however, livelihood strategies that include producing food for home consumption are expected to offer a measure of protection. To test this, we use anthropometric and consumption data from Indonesia collected before and after the 2007/08 food price crisis. Based on standardized height and weight measures, our results indicate that soaring food prices had a significant and negative impact on child growth among households that did not produce food for home consumption. A corresponding effect was undetectable for the households that did. The results remain robust when income effects from increased commercial sales, and possible attritions through migration and fostering are considered. Further, local food price changes were uncorrelated with the share of producing-households in the village and the initial average child nutrition status in the village, suggesting that observed outcomes are directly attributable to market events and livelihood strategies. Gender differences were not detected. Our findings imply that the food price crises can have negative impacts on children, potentially leading to lifelong disadvantages. Livelihood choices that include food production provide protection against price hikes but may trap households on low income paths.